Determining Factors That Influence Continuous Intention to Use E-wallet Among Students in Malaysian University - Rosmaini TASMIN; Alia AZMIR; Ishaq JAAFAR (Communications of International Proceedings, 2023)
E-wallets are used all over the world and using an e-wallet enhances our quality of life and productivity. Despite Malaysia being a high-potential environment for e-wallet growth, the rate of users adopting it is slow. E-wallet adoption in Malaysia is still in its infancy. If the acceptability of the new technology idea of e-wallet is poor, particularly among young customers, the new technology concept could be failure. The purpose of this research is to determine the determining factors that influence continuous intention to use E-wallet and to measure the significant relationship between factor lead to E-wallet usage towards continuous intention to use E-wallet. A total of 214 sets of data were collected from UTHM students through an online survey. SPSS Data Analysis software has been used to analyze the collected data. Spearman’s Rho correlation was applied to analyze the factors that influence the continuous intention to use e-wallet. This study found that average mean value of government support was the highest, which is M = 4.3849, SD = 0.60633. Moreover, the results reveal all variables; namely trust, social influence, promotion and government support are positively correlated with users’ continuous intention. The findings evince that these key factors significantly influence users’ continuous intention of e-wallet in Malaysia.
Keywords: E-wallet; Mobile payment; Continuous intention; Trust; Promotion.